2022
DOI: 10.1177/00207314221122658
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Outbreak in Brazil: Health, Social, Political, and Economic Implications

Abstract: COVID-19 outbreak quickly spread to all corners of the globe. In Brazil, the outbreak was particularly frightening because it worsened existing health, political, economic, and social problems. The results already observed show the contagion ripple-spreading process across the country, causing the death of thousands of people each day and counting, added to a very serious wave of unemployment, scientific denial, and social precariousness. Based on this, this study reviews recent research that looked at the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 69 publications
1
26
0
1
Order By: Relevance
“…Based on the literature [31], we expected to found increased stress in remote workers. However, our ndings suggest that both groups are at risk of mental disorders, mainly at 12-months follow-up, in which the number of cases and deaths were extremely high in Brazil [32]. Thus, these ndings indicate that the mental health conditions may be a consequence of pandemic and the virus itself and not the work arrangement [33].…”
Section: Discussionmentioning
confidence: 62%
“…Based on the literature [31], we expected to found increased stress in remote workers. However, our ndings suggest that both groups are at risk of mental disorders, mainly at 12-months follow-up, in which the number of cases and deaths were extremely high in Brazil [32]. Thus, these ndings indicate that the mental health conditions may be a consequence of pandemic and the virus itself and not the work arrangement [33].…”
Section: Discussionmentioning
confidence: 62%
“…The virus was adaptive with new variants, it required new types of vaccines, and the experiences varied among people, communities, and countries. Additionally, several countries did not immediately comply with the general global response mechanisms thereby posing greater challenges for managing COVID‐19 (Engler et al, 2021; Hamisi et al, 2023; Sott et al, 2022; Yan et al, 2020). COVID‐19 required high levels of collaboration and coordination among multiple actors since no single modalities seem to have had a definitive solution.…”
Section: Covid‐19 Complexity and Management Consequencesmentioning
confidence: 99%
“…Thus, a fourth dose of vaccine was offered in some countries. Brazil began to provide a fourth dose of vaccine to the most vulnerable populations, including HCWs in March 2022 12 …”
Section: Introductionmentioning
confidence: 99%
“…Brazil began to provide a fourth dose of vaccine to the most vulnerable populations, including HCWs in March 2022. 12 We have monitored the antibody response of the same cohort of HCWs for every dose of the COVID-19 vaccine, during the three COVID-19 waves in Brazil. Previously we showed that CoronaVac (Sinovac) induced an antibody response against both the viral S and N proteins of SARS-CoV-2 that declined over time.…”
mentioning
confidence: 99%